(untitled) (Journal of the College of Basic Education, 2025)
The experiment was conducted during the agricultural season 2024-2025 in Baghdad at the College of Basic Education, Department of Science, to study the effect of spraying with garlic plant extract and sowing dates on some vegetative qualities of the fenugreek plant Trigonella foenum - graecum L . The experiment used two factors, the first factor included four concentrations of garlic plant extract (0,5,7,5,10) ml / l, while the second factor was the planting of fenugreek seeds with two dates, the first is October 11 and the second is November 20. The experiment was designed with complete random sectors RCBD And with three repeaters. The results of the treatment of plants with garlic plant extract showed a significant increase in the studied qualities, which included plant height, number of leaves, leaf area, total chlorophyll, and the highest rates of the studied qualities when spraying with garlic extract at a concentration of 10 ml / liter.